Finger systolic pressure: its use in screening for hypertension and monitoring. Issue 6550 (27th September 1986) - Close, A; Hamilton, G; Muriss, S
Abstract : A finger sphygmomanometer was compared with a mercury column sphygmomanometer for its ability to screen for hypertension. A total of 881 patients used each machine, both in initial screening and then for monitoring. The finger sphygmomanometer had a specificity of 98.5% in routine screening as compared with 97.6% for the mercury column device. Sensitivity of the finger device was 98.2%. These findings suggest that the finger sphygmomanometer using finger systolic pressure alone is adequate for screening and monitoring blood pressure.